Surface modification of halloysite nanotubes grafted by dodecylamine and their application in reinforcing polytetrafluoroethylene. (24th May 2019) - Cheng, Zhi-Lin; Chang, Xing-Yu; Liu, Zan
Abstract: The modification of halloysite nanotubes (HNTs) as fillers is very effective at improving the performance of polymers. A novel modification of HNTs through grafting dodecylamine onto their surfaces was conducted here. Owing to the improvement in dispersibility of HNTs in polytetrafluoroethylene (PTFE), the mechanical properties and wear resistance (in particular) of the dodecylamine-modified HNT-filled PTFE composite were enhanced significantly.